Foreign Direct Investment and Violent Crimes: Evidence from the Iranian Provinces - gholamreza zamanian; Frnaz Dehghan; foruzan falahati; ali davari (پژوهشهای اقتصادی)
Aim and Introduction Today, with the expansion of globalization and increased economic competition, capital accumulation has been proposed as one of the main factors of the economic growth process of the countries, which can be provided through domestic or foreign sources. Meanwhile, inadequacy of internal resources and the need for high technical knowledge in some countries that seek economic growth have required a serious approach to this issue. Furthermore, countries with limited domestic resources are not able to expand exports and acquire shares from new markets, and they need stable resources to provide capital and their needs, among which attracting foreign capital is one of the economic solutions. Indirect foreign investment includes investments made by foreign natural and legal entities in the form of buying securities of a financial institution and company and providing them to the host country during a process. Due to the important role of foreign direct investment, the global market for attracting these funds has become really  competitive. Such competition has been formed especially among developing countries due lack of financial resources on the one hand, and the need for achieving rapid development on the other. Therefore, it is crucilaly important to identify the factors affecting the flow of foreign direct investment. As a result, the aim of the present study is to investigate the relationship between foreign investment and crimes committed in 31 provinces of the country during 2001-2021 using panel data regression models and unit root stationarity tests of Levin, Lin and Chu, Im, Pesaran and Shin, Fisher and Fisher. Methodology According to the theoretical foundations of foreign direct investment and crime and the study conducted by Daniele and Marani in 2008, regression model (panel data) and static test have been considered to investigate the relationship between foreign direct investment and crime. In other words, in the estimation of regression models in the form of time series, it is critically important to check the stationarity of the variables, and for this purpose, Levin, Lin and Chu, Im, Pesaran and Shin, Fisher and Fisher tests were used in this study. The variables investigated in this study include foreign direct investment as a dependent variable and population variables, GDP per capita, industry index, degree of openness of the regional economy, infrastructure index and crime variable as an independent variable. Findings The results indicate that the test of the first model shows a negative relationship between foreign direct investment and crime, which is not statistically significant. In other words, with the increase in crime, the power to attract foreign direct investment in each province decreases. The results of the second model indicate that the logarithm of GDP per capita has a negative and significant effect on the entry of foreign direct investment. In other words, with the increase of GDP in each province, the amount of foreign direct investment attraction decreases. In the third model, in addition to the gross domestic product, the logarithm of the investment of exploitation licenses issued in each province as an industry index of each province has been entered into the model, which has a negative and significant effect on foreign direct investment. In the fourth model, the variable related to the country's infrastructure, which in this study is the amount of electricity subscribers of each province, has a positive and significant effect, and by entering the infrastructure variable, the effect of other variables is the same as before. The variable of the degree of openness of the economy in the fifth model shows a positive and significant effect on foreign direct investment, and it shows that the more suitable the country has for trade with other countries, the more the desire to invest in the country increases and the more foreign direct investment is attracted. GDP per capita variables and industry index have a negative and significant effect, and the infrastructure variable also has a positive and significant effect on foreign direct investment. In final model where the population variable is entered, the results indicate a negative and significant effect of the population on foreign direct investment. In other words, with the increase in population, the power to attract direct investment in each province decreases. Discussion and Conclusion The results obtained from the present study indicate that although, based on the data examined in this study, crimes have not had a significant effect on the attraction of foreign direct investment, but the negative effects of GDP per capita and the industry index indicate that despite Iran's capabilities, it requires official and long-term planning to provide the necessary ground for attracting foreign direct investments. It seems that a step can be taken in this direction by applying the reduction of restrictions in the field of commercial policies, especially the foundation through tariff and customs policies and application of protective laws and regulations